TINJAUAN HUKUM ISLAM TERHADAP TRADISI MEURI’ BAGI WANITA HAMIL DI PAMBOANG MAJENE - Baharuddin; Kiljamilawati; Nur Aisyah (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2025)
This study discusses the Meuri’ tradition, a hereditary custom practiced by the Mandar community in Pamboang District, Majene Regency, specifically performed by pregnant women. The main focus of this research is to examine the tradition from the perspective of Islamic law. The sub-issues explored include the origin of the Meuri’ tradition, its implementation process, and how Islamic law views this practice. The research employs a qualitative method with sociological and Sharia approaches. Primary data were obtained through interviews with traditional leaders and local community members, while secondary data came from government documents and relevant literature. The findings show that Meuri’ is part of a traditional seven-month pregnancy ritual of the Mandar people, believed to bring blessings to both mother and fetus. The tradition begins with an intention, followed by consultation with a sando (traditional birth attendant) to determine the appropriate time for the ceremony, along with preparations of necessary items. Islamic elements in the tradition are reflected through the recitation of barzanji, salawat (praises to the Prophet), and the use of basmalah (invocation) at the start. This tradition embodies positive social and spiritual values. The study is expected to enrich local cultural references and encourage communities to maintain social bonds and reinforce Islamic values within cultural practices.